2020
DOI: 10.1017/s0029665120003237
|View full text |Cite
|
Sign up to set email alerts
|

An almond-enriched diet improves biomarkers of cardiometabolic health and increases alertness without changing cognitive performance in older overweight adults

Abstract: AbstractLongitudinal studies report that regular nut consumption is associated with reduced risk of coronary heart disease and better cognitive function. Thus, nuts may improve cardiovascular and neurocognitive health – especially in ‘at-risk’ populations (e.g. overweight/obese). This study examined the effect of supplementing habitual diets of overweight/obese individuals for 12 weeks with either almonds or carbohydrate rich (CHO-rich) snack foods on biomarkers of cardiovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Two PREDIMED sub-studies reported improvements in cognitive function in those participants randomized to a MedDiet intervention supplemented with 30 g/d mixed nuts after a mean of 6.5 y or 4.1 y, compared with those in the low-fat control diet arm [ 39 , 40 ]. The effects of different types of nut consumption (e.g., almonds [ 41 , 42 ], walnuts [ 19 ], and peanuts [ 43 ]) on cognitive performance and cognitive decline in middle-aged and older adults were inconsistent, either showing improvements in cognitive function [ 42 , 43 ] or no effect in delaying cognitive decline [ 19 , 41 ], but in no case was worse cognitive status observed compared with control diets. Some possible reasons for this inconsistency might be due to the duration of the interventions, the sample size studied, the background diets, the sociodemographic-economic and health status of the study populations, and most importantly, the overall risk of cognitive impairment/dementia, as persons at a higher risk (such as the PREDIMED-Plus population) are those that can benefit most from an intervention with neuroprotective agents such as certain nut components [ 18 , 19 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two PREDIMED sub-studies reported improvements in cognitive function in those participants randomized to a MedDiet intervention supplemented with 30 g/d mixed nuts after a mean of 6.5 y or 4.1 y, compared with those in the low-fat control diet arm [ 39 , 40 ]. The effects of different types of nut consumption (e.g., almonds [ 41 , 42 ], walnuts [ 19 ], and peanuts [ 43 ]) on cognitive performance and cognitive decline in middle-aged and older adults were inconsistent, either showing improvements in cognitive function [ 42 , 43 ] or no effect in delaying cognitive decline [ 19 , 41 ], but in no case was worse cognitive status observed compared with control diets. Some possible reasons for this inconsistency might be due to the duration of the interventions, the sample size studied, the background diets, the sociodemographic-economic and health status of the study populations, and most importantly, the overall risk of cognitive impairment/dementia, as persons at a higher risk (such as the PREDIMED-Plus population) are those that can benefit most from an intervention with neuroprotective agents such as certain nut components [ 18 , 19 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%